Green initiatives for mass rapid transit project in Malaysia / Thavamalar Krishnasamy - Thavamalar, Krishnasamy (2018)
In this study the green initiatives taken in the Mass Rapid Transit project in Malaysia are evaluated during the inception, construction and operation stages. This evaluation was made based on the information collected from the one of the MRT construction company and some of the information gathered through the survey and further studies. During the initial stages, the major environmental damage caused by deforestation or drastic land clearing and tree cutting. This has been reduced by rerouting the alignment of the track with minimum clearance and impact to the environment and also replaced those affected trees with new landscaping. During the construction period, the environmental damage was reduced by having various prevention strategies such as sustainable environment, sustainable energy, sustainable material and waste reduction system. During the operation stage, the carbon footprint was reduced by appropriate selection of material and efficient public transportation system which contributed 47% increase in productivity comparatively to other transportation mode such as cars and buses. Overall the MRT project, which began operations on December 2016 reduced carbon footprints by 82,305 tonnes CO2 per year in transporting a total of 146 million passengers. In addition, it is also expected to reduce 100,000 vehicles off the road and reduce traffic congestion in KL.